2020
DOI: 10.3390/nu12092730
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiometabolic Multimorbidity Pattern with Dietary Factors among Adults in South Korea

Abstract: Globally, cardiometabolic multimorbidity pattern (CMP) is a complex chronic health status that negatively effects the life expectancy of adults globally, even more than single diseases. We aimed to identify multimorbidity patterns in Korean adults to clarify the associations between dietary factors and CMP. Nationally representative data of 9011 Korean adults aged 19–64 years were obtained from the Korean National Health and Nutrition Examination Survey (KNHANES) from the period 2013 to 2015. Multimorbidity pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Regarding the relationship between dietary factors and NCD multimorbidty, the literature is limited and inconclusive [ 50 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. Inverse associations between vegetable and fruits consumption and NCD multimorbidity have been documented in cross-sectional [ 130 , 131 ] and longitudinal [ 132 , 133 , 134 ] studies. The harmful effect of soft drink consumption on multimorbidity was reported in an Australian study (n = 36,663, aged ≥ 16 years, 51.1% women) [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between dietary factors and NCD multimorbidty, the literature is limited and inconclusive [ 50 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. Inverse associations between vegetable and fruits consumption and NCD multimorbidity have been documented in cross-sectional [ 130 , 131 ] and longitudinal [ 132 , 133 , 134 ] studies. The harmful effect of soft drink consumption on multimorbidity was reported in an Australian study (n = 36,663, aged ≥ 16 years, 51.1% women) [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies investigating the association between dietary factors and multimorbidity [ 94 , 95 , 96 , 97 , 98 ], particularly in middle-aged women. Shi et al (2014) reported that the relative odds of multimorbidity were increased for those who consumed soft drink > 0.5 litre per day compared with those who did not consume soft drinks (OR: 2.03; 95% CI: 1.68, 2.45) [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al (2014) reported that the relative odds of multimorbidity were increased for those who consumed soft drink > 0.5 litre per day compared with those who did not consume soft drinks (OR: 2.03; 95% CI: 1.68, 2.45) [ 94 ]. Protective effects of fruit and vegetable consumption on multimorbidity have been observed in cross-sectional [ 95 , 96 ] and prospective [ 97 , 98 , 99 ] studies. Among European participants, the relative odds of multimorbidity decreased for those who adhered to modified MDS compared with who did not [ 40 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we performed multiple linear regressions on the three reduced factors that were derived from the 23 nutrient intake variables by factor analysis. The objective of the factor analysis was to convert sets of correlated variables into a few non-correlated variables, which allows for more accurate models [43,44]. The multiple linear regression models along with the three factors were applied to the men, women, and overall groups.…”
Section: Discussionmentioning
confidence: 99%